Cover Picture: Plasma Process. Polym. 1/2020. Issue 1 (2nd January 2020) - Schäfer, Jan; Quade, Antje; Abrams, Kerry J.; Sigeneger, Florian; Becker, Markus M.; Majewski, Candice; Rodenburg, Cornelia
Abstract : Outside Front Cover : Outside Front Cover: A novel plasma source 'HelixJet', operated at atmospheric pressure is introduced. Double helix electrodes driven by a radio frequency power supply generate a homogeneous glow discharge in a large volume quartz pipe. This renders the 'HelixJet' as a potential new additive manufacturing tool, in which polyamide powders can be simultaneously surface treated and partially melted to enable plasma‐based 3D printing of powders usually used in Laser Sintering. Further details can be found in the article by Jan Schäfer, Antje Quade, Kerry J. Abrams, et al. (1900099 ).